2021
DOI: 10.1038/s41467-021-21571-z
|View full text |Cite
|
Sign up to set email alerts
|

Probing intramolecular vibronic coupling through vibronic-state imaging

Abstract: Vibronic coupling is a central issue in molecular spectroscopy. Here we investigate vibronic coupling within a single pentacene molecule in real space by imaging the spatial distribution of single-molecule electroluminescence via highly localized excitation of tunneling electrons in a controlled plasmonic junction. The observed two-spot orientation for certain vibronic-state imaging is found to be evidently different from the purely electronic 0–0 transition, rotated by 90°, which reflects the change in the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…It is known to us that the electron-vibration coupling dominates the FWHM of the emission band when large-amplitude nuclear rearrangement in the S1 state has been suppressed. [10][11][12][13] To better understand the excellent color purity achieved by the tCzphBs, the vibrationally-resolved fluorescence spectra were simulated by TD-DFT at the PBE0/6-31g (d, p) level and compared with DtBuCzB (Fig. 3c, 3d, and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known to us that the electron-vibration coupling dominates the FWHM of the emission band when large-amplitude nuclear rearrangement in the S1 state has been suppressed. [10][11][12][13] To better understand the excellent color purity achieved by the tCzphBs, the vibrationally-resolved fluorescence spectra were simulated by TD-DFT at the PBE0/6-31g (d, p) level and compared with DtBuCzB (Fig. 3c, 3d, and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we believe that this multi-lock strategy for MR-TADF materials could be used for the development of narrowband organic emitters with full-color emissions, as well as high EL efficiency and stability. The 1 H and 13 C NMR chemical shifts were expressed as δ downfield using tetramethylsilane (TMS) as internal reference. Mass spectra were recorded by Thermo Scientific ISQ TM EC single quadrupole mass spectrometer using positive ion electrospray ionization (ESI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, accurate values of the simulated wavenumbers require mode-specific correction terms. Besides conformational changes, one might consider a redistribution of intensities between vibronic lines caused by 13 C substitution of individual carbon atoms in DBT and by Herzberg-Teller effects 56,[89][90][91] . The probability of 13 C substitution is about 28% in a DBT molecule and the effect on the vibronic spectrum depends on the exact substitution site.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important goals in nano-optics is to build nanoscale molecular switches with controlled photon emissions. , Such functional optical devices possess great application potentials in areas ranging from optical data storage/memories to nanoscale light sources. The developments of experimental techniques have made it possible to build actual nanodevices with single molecules as functional units. , Especially, it has been shown that the tunneling electrons in biased metallic junctions such as in a scanning tunneling microscope (STM) could be applied to induce electroluminescence (EL) from single molecules. , These advanced techniques thus opened the door for the design and validation of single-molecule based optical switches at the nanometer scale.…”
mentioning
confidence: 99%